Implementation of Hardship Principles on Financing Agreements Islamic Bank Due to Corona Virus Disease 2019 - Ashar Sinilele; Suriyadi Suriyadi; Syahrul Alim (Universitas Ahmad Dahlan, 2022)
Introduction to The Problem: This research analyzes covid-19, designated a disaster by the Indonesian government, especially its correlation to finance agreements in Islamic banks. The determination of disaster raises the question of whether covid-19 is a force majeure or hardship. According to Financial Service Authority (OJK), non-performing financing in Islamic banks is increased. Implementation of Force majeure principle to finance agreement in Islamic bank as a government policy is not right decision.Purpose/Objective Study: this legal research aims to analyze the effects of the coronavirus disease 2019 on finance agreements in Islamic banks and how is the implementation due covid-19 to renegotiation of finance agreement force majeure principle or hardship principle.Design/Methodology/Approach: This legal research is a normative legal study with two approaches: statute and conceptual approaches. Primary sources from Finance agreements in Islamic banks and statutes/rules. Secondary sources are books, journals, research, and dictionary. The legal analysis is carried out by classification of primary and secondary sources using the statute and conceptual approaches.Findings: The spread of the covid-19 virus has had many impacts on the ability of Islamic bank debtors to carry out their achievements due to the difficult conditions experienced due to restrictions by the government. The determination of the status of covid-19 as a disaster has implications for the occurrence of forced circumstances, so it is necessary to make adjustments to the situation based on the principle of hardship for financing agreements with Islamic banks. The occurrence of hardship for sharia bank customers provides an opportunity for customers to apply for contract renegotiation in the context of adjusting problematic contracts in the form of rescheduling, reconditioning, or restructuringPaper Type: Research Article